Moving Together: Developing and Testing the Impact of a Technology-Driven Intergenerational Intervention. A Pragmatic Evaluation - RACHEL KNIGHT (2021)
The phenomenon of intergenerational contact and the ability it may have to facilitate benefits for both older adults and children, often attracts attention. However, it is an underexplored concept, primarily underpinned by anecdotal evidence. This thesis aimed to develop and investigate the potential impact of a familial intergenerational technology-driven intervention on physical activity levels, sedentary behaviour, health-related quality of life, and stereotypes of ageing in older adults, aged ≥ 60 years old, in a real-world setting. Through the rigorous application of the stages of an individualised, iterative, multi-stage process model, justification of approach was confirmed, a unique intervention designed and refined, the incorporated behaviour change techniques mapped out, and, the feasibility, acceptability, functionality, and useability of the intervention and approach established. The developed intervention interlinked several discrete elements to allow intergenerational dyads, comprised of older adults (aged ≥ 60 years), and children (aged 7-11 years), to work collaboratively, using activity trackers (Mi Band 2) to complete virtual walk route challenges via the World Walking platform. Despite the limitations imposed by the COVID-19 pandemic, it was clearly established that: i) Age stereotype-based interventions provide an encouraging approach to challenging the health-related behaviour of older adults; ii) Through the components of Contact Theory (Allport, 1954), intergenerational contact and technology already available within the public domain, can be innovatively entwined to formulate health behaviour change intervention strategies; iii) Intergenerational contact provides mutual benefits for older adults and children, and, iv) The intervention developed was acceptable, useable, and potentially a highly feasible way of empirically exploring the impact of intergenerational contact, challenging age stereotypes, and positively affecting physical activity levels, sedentary behaviour, and health-related quality of life. Indeed, where depictions of later life have historically been negative, intergenerational contact provides an avenue to challenge such beliefs and behaviours.